Potential of Antagonistic Fungi in Inhibiting the Growth of Botryodiplodia theobromae Fungi Causes Stem Rot Disease in Citrus - Dina Agustina; unun triasih; mutia erti dwiastuti; rudi cahyo wicaksono (Universitas Djuanda Bogor, 2019)
Soil microorganisms such as Trichoderma asperellum and Gliocladium sp have the potential to become biological control agents in inhibiting the growth of fungi Botryodiplodia theobrome which causes stem rot disease in citrus plants. The purpose of this study was to determine the potential of T.asperellum and Gliocladium sp fungi in inhibiting the growth of B. theobrome fungus causing stem end rot disease in citrus plants. The antagonistic test was carried out using the dual culture method using PDA media; observations were made on the growth of pathogenic fungi and antagonistic fungi to measure their inhibitory power. The results of the observation and calculation of the fungal growth rate were analyzed using the T test with a level of 5%. The pathogen fungal growth rate in the antagonistic test was slower than control and inhibition of B. theobrome by T.asperellum and Gliocladium sp were respectively at 78.67% and 84.56%. The mechanism of the two antagonistic fungi has the nature of competition and parasitism because of the broader inhibition spectrum than the pathogenic fungi. Keywords: Botryodiplodia theobromae, Trichoderma asperellum, Gliocladium sp, antagonistic test.